Self-attraction and loading effects on ocean mass redistribution at monthly and longer time scales - Quinn, K. J. (2012)
Self-attraction and loading (SAL) effects caused by changes in mass loads associated with land hydrology, atmospheric pressure, and ocean dynamics produce time-varying, nonuniform spatial patterns in ocean bottom pressure (OBP). Such mass redistribution produced by SAL effects is shown to be an important component of OBP variability on scales from months to years and to provide for a better description of the OBP annual cycle observed by GRACE (Gravity Recovery and Climate Experiment). The SAL-induced ocean mass variations have magnitudes comparable to the dynamic OBP signals at subannual, annual, and interannual time scales in many ocean regions and should not be ignored in studies of ocean mass. Annual variations account for the most variability in SAL-related mass signals and can be induced by all the loads considered, with hydrology having the largest contribution. At subannual and interannual time scales, impact of hydrology is minimal and variations are mostly related to load changes from ocean dynamics and from changes in atmospheric circulation, depending on ocean region. The results demonstrate that the large-scale SAL effects are not negligible in the analysis of GRACE-derived global observations of OBP. The estimated SAL effects can explain on average 0.2 cm2 (16%) of the variance in the GRACE annual cycle (expressed in terms of equivalent water height), exceeding 1 cm2 in both open ocean and coastal regions with strong annual SAL signals.